2008
DOI: 10.1107/s1600536808041780
|View full text |Cite
|
Sign up to set email alerts
|

(E)-1-(4-Bromophenyl)-3-(3,4,5-trimethoxyphenyl)prop-2-en-1-one

Abstract: In the title compound, C18H17BrO4, the dihedral angle between the 4-bromo­phenyl and 3,4,5-trimethoxy­phenyl rings is 44.18 (6)°. In the crystal structure, the mol­ecules are linked by C—H⋯O and C—H⋯π inter­actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…The carbothioamide is slightly twisted from the pyrazole ring as indicated by the torsions angles N4-C18-N2-N1 = 5.51 (14)° and S1-C18-N2-N1 = -172.28 (7)°. The bond distances agree with the literature values (Allen et al, 1987) and are comparable to those observed in related structures (Chantrapromma et al, 2009;Suwunwong et al, 2009).…”
Section: Data Collectionsupporting
confidence: 90%
See 1 more Smart Citation
“…The carbothioamide is slightly twisted from the pyrazole ring as indicated by the torsions angles N4-C18-N2-N1 = 5.51 (14)° and S1-C18-N2-N1 = -172.28 (7)°. The bond distances agree with the literature values (Allen et al, 1987) and are comparable to those observed in related structures (Chantrapromma et al, 2009;Suwunwong et al, 2009).…”
Section: Data Collectionsupporting
confidence: 90%
“…For background to chalcone synthesis and the biological activity of pyrazole derivatives, see: Bekhit et al (2008); Ono et al (2007); Cottineau et al (2002); Gadakh et al (2010); Hall et al (2008); Hoepping et al (2007); Mikhaylichenko et al (2009); Park et al (2005) Souza et al (2002); Xie et al (2008). For related structures, see; Chantrapromma et al (2009); Suwunwong et al (2009). For the stability of the temperature controller used in the data collection, see Cosier & Glazer (1986).…”
Section: Related Literaturementioning
confidence: 99%
“…1 (Bernstein et al, 1995) (Table 1). The bond distances have of normal values (Allen et al, 1987) and are comparable with closely related structures (Suwunwong et al, 2009;Fun et al, 2010).…”
Section: Data Collectionmentioning
confidence: 54%
“…They have a wide range of applications including non-linear optical effects (Patil & Dharmaprakash, 2008) in fluorescent materials (Jung et al, 2008) and have biological activities such as antibacterial (Liu et al, 2011), anti-inflammatory (Lee et al, 2006), antileishmanial (Boeck et al, 2006), cytotoxic (Saydam et al, 2003), anti-oxidant (Cheng et al, 2008), HIV-1 protease inhibitory (Tewtrakul et al, 2003) as well as anti-tyrosinase activities (Nerya et al, 2004). The various interesting applications of chalcones lead us to synthesize the title chalcone derivative in order to study its tyrosinase inhibitory activity and also to compare its properies with the previously published related compounds (Suwunwong et al, 2009;Fun et al, 2010). Our experiment shows that (I) exhibits tyrosinase inhibitory activity with the IC 50 value of 0.075 ± 0.000 mg ml -1 .…”
Section: Data Collectionmentioning
confidence: 96%
See 1 more Smart Citation